2013
DOI: 10.1371/journal.pone.0069993
|View full text |Cite
|
Sign up to set email alerts
|

The Q175 Mouse Model of Huntington’s Disease Shows Gene Dosage- and Age-Related Decline in Circadian Rhythms of Activity and Sleep

Abstract: Sleep and circadian disruptions are commonly reported by patients with neurodegenerative diseases, suggesting these may be an endophenotype of the disorders. Several mouse models of Huntington’s disease (HD) that recapitulate the disease progression and motor dysfunction of HD also exhibit sleep and circadian rhythm disruption. Of these, the strongest effects are observed in the transgenic models with multiple copies of mutant huntingtin gene. For developing treatments of the human disease, knock-in (KI) model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
117
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 82 publications
(125 citation statements)
references
References 46 publications
8
117
0
Order By: Relevance
“…These findings were unexpected since the C57BL/6 background mice show normal physiological gating (Amann et al, 2010;Stevens et al, 1996), and a clear gene-dose effect was predicted on auditory gating in these mice. Although Q175 mice have been successfully used in various preclinical studies since they display a number of cardinal symptoms and pathophysiology of Huntington's disease (Loh et al, 2013), it seems they are less suitable for recapturing auditory gating abnormalities present in Huntington's disease. Furthermore, PF-04447943 did not improve either cortical or hippocampal auditory gating deficit at an efficacious dose in either WT or TG Q175 mice, although each group showed poor baseline gating.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were unexpected since the C57BL/6 background mice show normal physiological gating (Amann et al, 2010;Stevens et al, 1996), and a clear gene-dose effect was predicted on auditory gating in these mice. Although Q175 mice have been successfully used in various preclinical studies since they display a number of cardinal symptoms and pathophysiology of Huntington's disease (Loh et al, 2013), it seems they are less suitable for recapturing auditory gating abnormalities present in Huntington's disease. Furthermore, PF-04447943 did not improve either cortical or hippocampal auditory gating deficit at an efficacious dose in either WT or TG Q175 mice, although each group showed poor baseline gating.…”
Section: Discussionmentioning
confidence: 99%
“…Methods used were similar to those described previously (Loh et al, 2013). Male Mecp2 −/y mutant mice and WT littermates (7-8 weeks old) were housed in 12:12 LD conditions.…”
Section: Immobility-defined Sleep Assaymentioning
confidence: 99%
“…Methods used were similar to those described previously (Kudo et al, 2011;Loh et al, 2013). Male Mecp2 −/y mutant mice and WT littermates were housed in cages containing running wheels (Mini Mitter Co., Bend, OR) from 6 to 7 weeks of age and their wheelrunning activity recorded as revolutions (rev) per 3 min intervals.…”
Section: Wheel Running Activity Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Although pathogenic pathways are beginning to be unraveled offering targets for treatment,8 the precise pathophysiological mechanisms of HD are poorly understood 9. Previously we have shown that sleep disturbances are present in early manifest disease,10 and several studies on transgenic animal models of HD have shown that sleep progressively worsens as the disease develops11, 12, 13, 14 dependently on age and gene dosage 15. However, we do not know whether sleep problems are present during the premanifest stage in individuals carrying the HD gene mutation.…”
mentioning
confidence: 99%